2011
DOI: 10.5761/atcs.oa.10.01558
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis-patient Mismatch after Mitral Valve Replacement Stratified by Referred and Measured Effective Valve Area

Abstract: Objective: The aim of this study was to determine the impact of patient-prosthesis mismatch (PPM) after mitral valve replacement (MVR) on the late clinical outcome, evaluated from the referred value and measured mitral valve area in the echocardiograph. Patients and Method: The records of 212 patients who underwent MVR between 1995 and 2008 at Funabashi Municipal Medical Center, Japan were studied retrospectively. Exclusions were patients who had a repeat MVR or concomitant aortic valve surgery. Of 212 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…On the contrary, other studies did not detect a deleterious impact of PPM on long-term survival after MVR [11][12][13]15]; however, there is apparently an interaction between preoperative PH and long-term outcome in patients with both moderate and severe PPM [2,3]. In our series, not only patients with severe mitral PPM associated or not to preoperative PH but also those presenting moderate mismatch with preoperative systolic pulmonary pressure > 55 mm Hg showed lower long-term survival.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…On the contrary, other studies did not detect a deleterious impact of PPM on long-term survival after MVR [11][12][13]15]; however, there is apparently an interaction between preoperative PH and long-term outcome in patients with both moderate and severe PPM [2,3]. In our series, not only patients with severe mitral PPM associated or not to preoperative PH but also those presenting moderate mismatch with preoperative systolic pulmonary pressure > 55 mm Hg showed lower long-term survival.…”
Section: Discussionmentioning
confidence: 58%
“…When considering values lower than 1.2 cm 2 /m 2 to define PPM, Bouchard et al [14] found only 3.7% of mismatch in patients receiving a mechanical valve. In contrast, Matsuura et al [11] found 58.9% of PPM with the same cut-off value, including mechanical prostheses and approximately one-third of bioprosthesis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…1-6 Risks for failure of the maze procedure and short-term recurrence of AF, however, have been reported, 1,7 while few studies of predictors of late recurrence of AF after the maze procedure have been presented. Prosthesis-patient mismatch (PPM) after mitral valve replacement (MVR) has recently become a topic of interest, [8][9][10][11][12][13][14] with mixed results reported regarding the effects of PPM after MVR on late cardiac outcome and long-term survival. The aim of this study was to determine the impact of PPM after MVR with a cryomaze procedure.…”
Section: Methodsmentioning
confidence: 99%
“…14 The American College of Cardiology/American Heart Association (ACC/ AHA) guidelines define moderate mitral stenosis as mean MPG=5-10 mmHg, 15 while we defined mean MPG >5 mmHg as high mean MPG.…”
mentioning
confidence: 99%